2020
DOI: 10.2118/203845-pa
|View full text |Cite
|
Sign up to set email alerts
|

Direct Injection of Biomineralizing Agents to Restore Injectivity and Wellbore Integrity

Abstract: Summary In this manuscript, we describe the second of two field demonstrations of microbially induced calcium carbonate precipitation (MICP) performed in a failed waterflood injection well in Indiana. In 2012, fracture-related flow pathways developed in the wellbore cement, causing injection water to bypass the oil-bearing formation and enter a high-permeability sandstone thief zone, thereby substantially decreasing injection pressure. In the first field demonstration, our study team characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Introduction of Biomineralization/MICP. Biomineralization or microbial-induced calcium carbonate (CaCO 3 ) precipitation (MICP) technology has been widely developed for applications in numerous areas such as sealing of cement fractures through generating surface coatings or reinforcing cement, 214 decreasing the mobility in high-permeability layers or channels, 215,216 consolidating the permeable media, and so on. Biofilm sealants (i.e., MICP or biofilm barrier) involve urea, Ca 2+ , nutrient feed, and microorganisms.…”
Section: Advantages and Limitationsmentioning
confidence: 99%
“…Introduction of Biomineralization/MICP. Biomineralization or microbial-induced calcium carbonate (CaCO 3 ) precipitation (MICP) technology has been widely developed for applications in numerous areas such as sealing of cement fractures through generating surface coatings or reinforcing cement, 214 decreasing the mobility in high-permeability layers or channels, 215,216 consolidating the permeable media, and so on. Biofilm sealants (i.e., MICP or biofilm barrier) involve urea, Ca 2+ , nutrient feed, and microorganisms.…”
Section: Advantages and Limitationsmentioning
confidence: 99%
“…Ureolytic microbially induced carbonate precipitation (MICP) has been studied extensively for over two decades. Owing to the low viscosity of MICP reagents, particular interest has emerged around subsurface applications, including immobilization of divalent heavy metals and radionuclides in groundwater, , as well as trapping enhancement and wellbore leakage mitigation at geological CO 2 sequestration sites. Bioaugmentation using Sporosarcina pasteurii (S.…”
Section: Introductionmentioning
confidence: 99%
“…Microbes that break down urea Because of its ability to manufacture the urease enzyme, Sporosarcina pasteurii , nonpathogenic bacteria species, has been extensively tested for the induction of calcium carbonate precipitation [11]. Only a few studies have revealed that ureolytic bacteria such as Variovorax boronicumulans and Stenotrophomonas rhizophila are involved in metal biomineralization [12]. MICP is a method for replacing calcium with other divalent elements and achieving substantial heavy metal absorption at the surface and inside the calcite lattice.…”
Section: Introductionmentioning
confidence: 99%
“…In subsurface porous media environments, MICP may be arbitrated by devoted microorganisms, called biofilms. MICP also known as biofilm‐mediated calcite precipitation, happens when microbial metabolism modifies the nearby aqueous stage in a method that causes calcite to precipitate [12]. Biofilm‐forming bacteria's capability to build complex structures is reliant on their organic extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%